2021
DOI: 10.3390/nu13020455
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Early Childhood Caries in Children under 5 Years Old in the European Union and Associated Risk Factors: An Ecological Study

Abstract: The associations among early childhood caries (ECC), socioeconomic status, and sugar consumption are of the utmost importance, due to their potential policy implications. The purpose of this study was to identify trends in ECC burden in children under 5 years old among European Union (EU) member states over time and to evaluate the relationship with its risk factors. Global Burden of Disease 2019 data were analyzed to estimate the burden of ECC over time, specifically incidence, prevalence, and years lived wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…Primary teeth caries rates in Poland are lower than in developing countries but higher than in more economically developed parts of European Union [ 27 ]. In 2016, national oral health monitoring revealed that 89.4% of 7-year-old children were affected by dental caries with a mean dmft index equal to 5.61 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary teeth caries rates in Poland are lower than in developing countries but higher than in more economically developed parts of European Union [ 27 ]. In 2016, national oral health monitoring revealed that 89.4% of 7-year-old children were affected by dental caries with a mean dmft index equal to 5.61 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern research on caries has indicated that the non-dental risks of ECC may include a low level of SES, other vulnerable sub-populations with disparities, and/or certain minority ethnical vs. racial groups, etc. [13][14][15][16][17][18][19][20][21][22][23][24][25]. Therefore, there is an urgent need to identify the critical risks of ECC and also target the high-risk sub-populations on prevention and effective protocols for subsequent proper treatments vs. managements.…”
Section: Discussionmentioning
confidence: 99%
“…The ECC-psychomotor axial interactions are complex, where the causal factors, risks, confounding variable(s), or interference may be intertwined [10][11][12][13][14][15][16][17]. Notably, there were three distinct characteristics in our present cohorts analyzed (Table 1): (i) there were insignificant healthcare inequity issues involved, due to the national healthcare insurance program available; (ii) the kindergartener family cohorts had annual income levels of the middle class, based on the SES gradients of the regions addressed; and (iii) the kindergarteners recruited and enrolled for the study all came from the regular/normal classes of preschoolers without any special or disabled children involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations